Analysis of Hotel Visitor Reviews using LDA-Based Topic Modeling Method - Bunga Aisyah Ravissangeta Yansari; Nurvita Trianasari (Almana : Jurnal Manajemen dan Bisnis, 2021)
In the current era, many challenges must be faced by tourism businesses in the field of hospitality. The customer experience is an important factor in creating a hotel's reputation because customers can provide feedback online. Agoda is a company that provides an online booking system with online review features including reviews from visitors to Hotel Golden Flower Bandung. This research aims to identify topics that are often discussed related to the experience of staying visitors at The Golden Flower Hotel Bandung and to identify marketing tactics that must be done by the hotel. Secondary data is obtained by doing web scrapping using the Parsehub application. The data sources used are all golden flower hotel Bandung visitor reviews available on Agoda's website. This study shows the topic covered in the overall visitor review on Agoda's website is an expression of satisfaction with hotel services and facilities. Golden Flower Hotel Bandung can maintain the quality of services and facilities that get a lot of expressions of visitor satisfaction and improve services and facilities that get a lot of expressions of disappointment from the visitor experience as well as offer new strategies that are more responsible and conduct customer-centered marketing.